Learning from errors: A model of individual processes - Tulis, Maria; Steuer, Gabriele; Dresel, Markus (Frontline Learning Research, 2016)
Errors bear the potential to improve knowledge acquisition, provided that learners are able to deal with them in an adaptive and reflexive manner. However, learners experience a host of different—often impeding or maladaptive—emotional and motivational states in the face of academic errors. Research has made few attempts to develop a theory that focuses on learning from errors (with the exceptions of the theory of impasse-driven learning and the theory of negative knowledge) and, in particular, a theoretical framework that focuses on antecedent motivational processes. By integrating theories of self-regulated learning, volition, attributions, and appraisals, we propose a model that highlights individual processes that are characteristic of this specific learning phenomenon. More precisely, our theoretical framework aims to explain how emotional, motivational and self-regulatory processes—influenced by personal and contextual conditions—interact in order to facilitate or impede adaptive dealing with errors and appropriate metacognitions and cognitive activities. Our objective is to provide a framework that allows for the systematic integration of various aspects that have been targeted in previous research and to guide and stimulate future research on learning from errors. As a first evidence for validation, we summarise research findings that address specific parts of the proposed model.